2012
DOI: 10.1038/ng.1051
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analyses identify 13 loci associated with age at menopause and highlight DNA repair and immune pathways

Abstract: To identify novel loci for age at natural menopause, we performed a meta-analysis of 22 genome-wide association studies in 38,968 women of European descent, with replication in up to 14,435 women. In addition to four known loci, we identified 13 new age at natural menopause loci (P < 5 × 10−8). The new loci included genes implicated in DNA repair (EXO1, HELQ, UIMC1, FAM175A, FANCI, TLK1, POLG, PRIM1) and immune function (IL11, NLRP11, BAT2). Gene-set enrichment pathway analyses using the full GWAS dataset iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
334
6
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 334 publications
(352 citation statements)
references
References 80 publications
11
334
6
1
Order By: Relevance
“…The coding-synonymous SNP rs365132, in the ubiquitin interaction motif-containing 1 gene (UIMC1), is an expression-quantitative trait locus for nearby genes FGFR4 and ZNF346 in the cortex. UIMC1 functions in DNA repair via interaction with BRCA1 and estrogen receptor α (Stolk et al 2012). BRSK1 is an AMPactivated protein kinase (AMPK)-related serine/ threonine kinase, which regulates neurotransmitter release at the axonal terminals (Inoue et al 2006).…”
Section: −8mentioning
confidence: 99%
See 1 more Smart Citation
“…The coding-synonymous SNP rs365132, in the ubiquitin interaction motif-containing 1 gene (UIMC1), is an expression-quantitative trait locus for nearby genes FGFR4 and ZNF346 in the cortex. UIMC1 functions in DNA repair via interaction with BRCA1 and estrogen receptor α (Stolk et al 2012). BRSK1 is an AMPactivated protein kinase (AMPK)-related serine/ threonine kinase, which regulates neurotransmitter release at the axonal terminals (Inoue et al 2006).…”
Section: −8mentioning
confidence: 99%
“…It has been well recognized that genetic makeup influences both AM (Sharma 2002;Anderson et al 2008) and ANM (de Bruin et al 2001;Murabito et al 2005;Morris et al 2011). Recent genome-wide association studies (GWASs) among women of European ancestry have identified at least 106 genetic loci for AM (He et al 2009;Ong et al 2009;Perry et al 2009;Sulem et al 2009;Elks et al 2010;Perry et al 2014) and 21 loci for ANM (He et al 2009;Stolk et al 2009;Stolk et al 2012). However, only 24 AM loci and 9 ANM loci have been replicated in women of either Asian or African ancestry and no novel loci have been identified in these non-European populations (Liu et al 2009;Chen et al 2012;Shen et al 2013;Spencer et al 2013;Tanikawa et al 2013;Delahanty et al 2013;Carty et al 2013;Demerath et al 2013;Pyun et al 2014;Chen et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In this case, early menopause could be considered as only a marker of risk. In support of a shared genetic basis, a large-scale genome-wide association study of age at menopause identified a number of loci, including the ones relevant to CVD, that were involved in inflammatory response, oxidative stress and genome stability 22 . Speculative environmental factors could include obstetric history, such as parity or having a stillbirth.…”
Section: Interpretation Of Findingsmentioning
confidence: 99%
“…Age at menopause is determined by a combination of initial oocyte numbers and the rate of loss of ovarian follicles across the course of the female lifespan (Broekmans et al 2009;Bukovsky 2010;Hansen et al 2008;te Velde et al 1998) both of which can be influenced by genetic (Stolk et al 2012), environmental (Sakata et al 2011), and lifestyle factors (Gold et al 2001;Morris et al 2012). As a result, a wide range of variation in age at menopause has been documented across diverse populations (Henderson et al 2008;Johnston 2001;Reynolds and Obermeyer 2005;Sievert 2006; Thomas et al 2001).…”
Section: Introductionmentioning
confidence: 99%